DAMPAK MEDIA PEMBELAJARAN INFOGRAFIS TERHADAP PEMAHAMAN PENDIDIKAN PANCASILA: SEBUAH PENELITIAN QUASI-EKSPERIMENTAL - Dwi Cahyani , Mentari (YAYASAN PERCIKAN INSAN MANDIRI (PRISMA), 2024)
The purpose of this study was to determine whether there is an influence of teaching methods on students’ understanding in the subject of Pancasila Education. The study involved students from one class at Linggabuana PGRI University Sukabumi. The research method used was a quasi-experimental non-equivalent control group design with a pretest-posttest design. The results of the analysis showed that there was a significant difference between the control group and the experimental group in terms of students’ understanding in the subject of Pancasila Education. The experimental group showed a more significant improvement in the test compared to the control group. Based on these findings, it can be concluded that infographic-based instructional media have a positive influence on students' understanding in Pancasila Education. Infographics can enhance students' understanding of the concepts of Pancasila Education. The recommendation of this study is to widely implement infographic-based instructional media in teaching Pancasila Education to improve students’ understanding.